'What men don't know can hurt women's health': a qualitative study of the barriers to and opportunities for men's involvement in maternal healthcare in Ghana. Issue 1 (December 2015) - Ganle, John; Dery, Isaac
Abstract Background The importance of men's involvement in facilitating women's access to skilled maternal healthcare in patriarchal societies such as Ghana is increasingly being recognised. However, few studies have been conducted to examine men's involvement in issues of maternal healthcare, the barriers to men's involvement, and how best to actively involve men. The purpose of this paper is to explore the barriers to and opportunities for men's involvement in maternal healthcare in the Upper West Region of Ghana. Methods Qualitative focus group discussions, in-depth interviews and key informant interviews were conducted with adult men and women aged 20–50 in a total of seven communities in two geographic districts and across urban and rural areas in the Upper West Region of Ghana. Attride-Stirling's thematic network analysis framework was used to analyse and present the qualitative data. Results Findings suggest that although many men recognise the importance of skilled care during pregnancy and childbirth, and the benefits of their involvement, most did not actively involve themselves in issues of maternal healthcare unless complications set in during pregnancy or labour. Less than a quarter of male participants had ever accompanied their wives for antenatal care or postnatal care in a health facility. Four main barriers to men's involvement were identified: perceptions that pregnancy care is a female role while men are family providers; negative cultural beliefs such as the belief that men who accompany their wives to receive ANC services are being dominated by their wives; health services factors such as unfavourable opening hours of services, poor attitudes of healthcare providers such as maltreatment of women and their spouses and lack of space to accommodate male partners in health facilities; and the high cost associated with accompanying women to seek maternity care. Suggestions for addressing these barriers include community mobilisation programmes to promote greater male involvement, health education, effective leadership, and respectful and patient-centred care training for healthcare providers. Conclusions The findings in this paper highlight the need to address the barriers to men's involvement, engage men and women on issues of maternal health, and improve the healthcare systems – both in terms of facilities and attitudes of health staff - so that couples who wish to be together when accessing care can truly do so.